Analisis Korupsi yang Dilakukan Aparatur Sipil Negara (ASN): Tinjauan Hukum dalam Konteks Kepegawaian (Lembaga Pengembangan Kinerja Dosen, 2025)
Corruption committed by the State Civil Apparatus (ASN) is a deep problem, which requires a comprehensive study from the perspective of civil service law. This research aims to conduct an in-depth analysis of the phenomenon of corruption committed by ASN, by considering relevant aspects of civil service law. Through a legal review approach, this study includes an analysis of the laws and regulations governing ASN, specifically related to the code of ethics, governance, and personnel discipline regulations. This study also reveals the relationship between corruption behavior committed by ASN and the legal consequences that apply according to existing civil service regulations. The analysis is carried out to identify gaps or weaknesses in the civil service regulatory system that may be a driving factor for corruption among ASN. In addition, efforts or steps that can be taken to strengthen the civil service system to prevent and overcome acts of corruption in the ASN environment are also presented.